Allelic diversity of glutenins in rainfed bread wheat in Mexico - Martínez Cruz Eliel; Villaseñor Mir Héctor E.; Santa Rosa René Hortelano; Pérez Herrera Patricia; Rodríguez García Ma. Florencia; Espitia Rangel, Eduardo; Peña Bautista Roberto J. (Revista Mexicana de Ciencias Agrícolas, 2018)
The parent group from the rainfed wheat program in Mexico was characterized based on their high (HMW-G) and low (LMW-G) molecular weight glutenin variants. The HMW-G and LMW-G were identified by polyacrylamide gel electrophoresis. Frequencies were calculated for the Glu-A1, Glu-B1, Glu-D1, Glu-A3, Glu-B3 and Glu-D3 loci as well as for their HMW-G and LMW-G combinations. Greater polymorphism was observed in the Glu-B1 and Glu-B3 loci with 6 and 8 individual variants respectively. HMW-G alleles with higher frequency were 2* in Glu-A1, 17+18 in Glu-B1 and 5+10 in Glu-D1, and for LMW-G were the c variants in Glu-A3, h in Glu-B3 and b in Glu-D3. In the Glu-B1 and Glu-D1 loci two new alleles 7*+15 and 2+T2/1.5+T2 were identified. Furthermore the HMW-G combination with higher proportion were 2*, 17+18, 5+10 and for LMW-G c, h, b. Based on the above, there are alleles and HMW-G and LMW-G combinations in the parent group of rainfed bread wheat in Mexico, favoring progeny generation with suitable quality for the bakery, biscuit and pastry products preparation.